Treating onychomycosis with the short-pulsed 1064-nm-Nd: YAG laser: results of a prospective randomized controlled trial - Karsai, Syrus; Weiß, Christel; Schneider, Stefan W.; Raulin, Christian (Journal of the European Academy of Dermatology and Venereology, 2017)
Background The role of the short-pulsed 1064-nm-Nd:YAG laser in treating onychomycosis has been the subject of controversial discussion ever since it received FDA approval in 2010. Research to date provides no valid conclusions supporting its use from an evidence-based perspective. Objective In this prospective randomized controlled pilot study, we analysed the effect of the short-pulsed 1064-nm-Nd:YAG laser on the rate of mycological remission and clinical improvement after excluding relevant confounders with regard to our previous studies. Patients and methods Twenty patients with a total of 82 mycotic toenails were randomized to the treatment group (short-pulsed 1064-nm-Nd:YAG laser) or control group (no laser treatment). We conducted four laser treatments at 4- to 6-week intervals. In both groups, a local antimycotic agent was applied to the sole of the foot, the area between the toes and the skin directly surrounding the nails. The primary endpoint was complete remission of the onychomycosis after 12 months (fungal culture and histology); secondary endpoints included clinical improvement (Onychomycosis Severity Index, OSI) and the occurrence of pain or other adverse events. Results Mycological remission was not achieved in either study group. A comparison of both groups yielded no difference in the OSI score, both at the beginning of the trial (P = 0.9873) and after 12 months (P = 0.4317). In the treatment group, the OSI score worsened by a mean 2.0 points, and in the control group, by a mean 3.5 points. On a visual analogue scale (0 = ‘no pain’ to 10 = ‘most intense pain’), pain in the treatment group was indicated at a mean score of five. Other adverse events were not reported. Conclusions The short-pulsed 1064-nm-Nd:YAG laser shows no long-term efficacy as a monotherapy. Its role as an adjuvant therapy should be investigated in upcoming trials.
First published: 13 August 2016
Gesehen am 28.06.2018